Compound health risk assessment of cumulative heavy metal exposure: a case study of a village near a battery factory in Henan Province, China. Issue 6 (27th May 2020) - Jiang, Yuling; Ma, Jianhua; Ruan, Xinling; Chen, Xing
Abstract : The concentrations of the heavy metals Hg, As, Ni, Pb, Cd, Cr, Cu and Zn in soil, groundwater, air, and locally produced grain (wheat and corn) and vegetables were determined in a village near a battery factory in Xinxiang, Henan Province, China. Abstract : The concentrations of the heavy metals Hg, As, Ni, Pb, Cd, Cr, Cu and Zn in soil, groundwater, air, and locally produced grain (wheat and corn) and vegetables were determined in a village near a battery factory in Xinxiang, Henan Province, China. A multimedia, multipathway health risk assessment of heavy metal exposure was carried out using the health risk model recommended by the United States Environmental Protection Agency (US EPA). The results showed that the concentrations of Cd in soil, Cd and Pb in wheat, Hg in corn, Cd, Hg, and Pb in vegetables, and Cd and As in PM2.5, PM10, and TSP were all higher than the corresponding limits for heavy metals in China. The non-carcinogenic risks ( HI s) for all environmental media were higher in children than in adults, and the carcinogenic risks ( TCR s) of heavy metal exposure in other media except for soil were higher in adults than in children. The total HI and TCR in adults and children were higher than the standard limit values because of heavy metal exposure through soil, groundwater, PM10, grain and vegetables. Cd was the most significant heavy metal in terms of HI and TCR factors; among the evaluated pathways, the contribution of diet was the largest. The HI and TCR caused by dietary crops account for 96.7% and 98.9% of the total in adults and 90.2% and 96.2% of the total in children, respectively. To maintain the health of the residents in the study area, it is strongly recommended to stop planting edible agricultural products immediately, start buying grain and vegetables from outside the study area, and strictly strengthen the control of heavy metal pollution in the study area. The source apportionment results show that Cd, Ni and As were mainly from industrial sources, which was related to sewage irrigation and battery plant deposition, and Pb and Cr were mainly from agricultural activities.